2018
DOI: 10.1002/cam4.1744
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a high‐risk subtype of intestinal‐type Japanese gastric cancer by quantitative measurement of the luminal tumor proportion

Abstract: BackgroundWe hypothesized that the relative proportion of tumor (PoT) at the luminal surface can predict gastric cancer (GC) patient survival.MethodsWe measured the luminal PoT in resection specimens from 231 GC patients with stage II/III disease who had surgery at the Kanagawa Cancer Center, Yokohama, Japan. Tissue microarrays were used to assess the extent of immune cell infiltration by CD45 immunohistochemistry. Results were related to histopathological features and patient overall survival (OS).ResultsPoT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
(55 reference statements)
0
11
0
Order By: Relevance
“…In the present study, PPI and WGCNA networks revealed 6 common hub genes, including PTPRC, TYROBP, CCR1, C1QB, CYBB , and LCP2 . According to Wang et al ( 39 ), CYBB is associated with invasion and prognosis of human gastric cancer, whereas PTPRC , also known as CD45, has been previously used to assess the extent of immune cell infiltration in intestinal-type Japanese gastric cancer ( 40 ). On the other hand, Chen et al ( 41 ) previously reported that CCR1 was associated with CD4 + CD25 + Tregs of regional lymph nodes in forestomach carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, PPI and WGCNA networks revealed 6 common hub genes, including PTPRC, TYROBP, CCR1, C1QB, CYBB , and LCP2 . According to Wang et al ( 39 ), CYBB is associated with invasion and prognosis of human gastric cancer, whereas PTPRC , also known as CD45, has been previously used to assess the extent of immune cell infiltration in intestinal-type Japanese gastric cancer ( 40 ). On the other hand, Chen et al ( 41 ) previously reported that CCR1 was associated with CD4 + CD25 + Tregs of regional lymph nodes in forestomach carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…2a). To probe the limits of our proposed method, we validated the MSI detector on N=185 gastric cancer patients from Yokohama, Japan (KCCH cohort 19 ). Asian gastric cancer has a very different histology and clinical course than non-Asian gastric cancer 20 .…”
Section: Microsatellite Instability (Msi) Determines Whether Patientsmentioning
confidence: 99%
“…As an external CRC N DACH" control study on CRC in the southwest of Germany with long-term followed-up patients enrolled in more than 20 clinics of the study region. Also, we analyzed data of N=185 patients from Kanagawa Cancer Center, Yokohama, Japan (KCCH) as described previously 19 . More information about the cohorts is shown in Suppl.…”
Section: Tumor Detection Msi Detection and Patient Cohortsmentioning
confidence: 99%
“…Traditionally, the epithelial cell features of GC are the key components for the classification of histological types. In recent years, the microenvironment infiltrated immunocytes and intratumoral stroma, showing the potential prognostic value for the progress of tumors [13][14][15]. Xu et al [16] revealed that the high level of lymphocytemonocyte ratio (LMR) and high tumor-associated macrophage (TAM) infiltration in GC patients after radical resection, and the LMR and TAM are both independent prognostic factors for OS and recurrence-free survival of GC patients.…”
Section: Introductionmentioning
confidence: 99%